Youth Inclusion in Rural Transformation. Issue 4 (3rd April 2021) - Arslan, Aslihan; Tschirley, David L.; Di Nucci, Constanza; Winters, Paul
Abstract: The increasing numbers of rural youth in developing countries and their perceived disenchantment with the society and economy have raised policy concerns across the developed and developing world. Youth (ages 15 to 24) make up one in five people in developing countries, and one in eight in the developed world. Of the 1.2 billion youth in the world, nearly 1 billion reside in developing countries, and their numbers are growing far more rapidly than in higher-income countries. Despite the increasing number of institutional publications on youth issues, rigorous research to put these numbers into perspective and to shed light into their challenges and opportunities in economic, political and civic participation to guide their inclusion in rural transformation is remarkably limited. This special section brings together five papers that make use of the most up to date and comprehensive data sets and analyses on rural youth to address these research gaps. They provide an overall understanding of the contexts (economic sectors, spatial distributions, welfare outcomes, gendered differences, and civic participation) in which rural youth live and work, and expand the nascent literature that can support the design and targeting of policies to ensure rural youth inclusion in rural transformation.